Long non-coding RNA CCAT2 promotes oncogenesis in triple-negative breast cancer by regulating stemness of cancer cells. (February 2020) - Xu, Zhen; Liu, Cuiui; Zhao, Qian; Lü, Jinhui; Ding, Xin; Luo, An; He, Jia; Wang, Guangxue; Li, Yuan; Cai, Zhaoqing; Wang, Zhongrui; Liu, Junjun; et al.
Graphical abstract: Abstract: Triple-negative breast cancers (TNBC) are more aggressive due to lacking receptors for hormone therapy and maintaining stemness features in cancer cells. Herein we found long non-coding RNA CCAT2 overexpressed specially in TNBC, and in breast cancer stem cells (BCSC) as well. Enforced overexpression and targeted knockdown demonstrated the oncogenic function of CCAT2 both in vitro and in vivo . CCAT2 promoted the expression of stemness markers including OCT4, Nanog and KLF4, increased mammosphere formation and induced ALDH+ cancer stem cell population in TNBC. A chromosomally adjacent gene OCT4-PG1, as a pseudogene of OCT4, was upregulated by CCAT2, and positively regulated the stemness features of TNBC cells. miR-205 was identified as a target gene of CCAT2 in TNBC. Point-mutation in CCAT2 impaired the sponge inhibition of miR-205. Overexpression of miR-205 rescued the oncogenic phenotypes induced by CCAT2. In addition, Notch2, as a target gene of miR-205, was downregulated by miR-205 and upregulated by CCAT2 in TNBC. Collectively, the current study revealed a novel function of CCAT2 in promoting tumor initiation and progression in TNBC through upregulating OCT4-PG1 expression and activating Notch signaling. These findings not only demonstrated a lncRNA-based therapeutic strategy in treatment of TNBC, but also added a node to the regulatory network of CCAT2 that controls aggressiveness of breast cancer stem cells.